Prevalence of Thyroid Dysfunction in Community of Duwakot, Bhaktapur (Journal of Pathology of Nepal, 2017)
Background: Thyroid dysfunction is one of the major public health problems in the Nepalese community and of the common endocrine disorders diagnosed in community primary health care centres.  The aim of this study is to analyze the prevalence of Thyroid dysfunction in Duwakot, NepalMaterials and Methods:  All the patients from Duwakot community who presented with the history of weight gain with tiredness and weight loss with palpitation were subjected to thyroid function test free triiodothyronine, free thyroxine and thyroid stimulating hormone. Results: Thyroid dysfunction was  found in 26% with M:F ratio of 1:5.  Subclinical hypothyroidism 62 (11.44%) was the most prevalent one followed by Primary hypothyroidism  48 (8.85%), primary hyperthyroidism 16 (2.95%) and subclinical hyperthyroidism 15 (2.76%).Conclusion: Thyroid dysfuntion has been observed despite of nationwide program regarding supplementation of micronutrient iodised salt.  Key words: Euthyroid, Hyperthroidism, Hypothyroidism, Iodine, Prevalence, Thyroid dysfunction